Intracranial Hypertension and Cerebral Malaria - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Intracranial pressure (ICP) was monitored and cerebral perfusion pressure (CPP) calculated in 23 African children suffering from cerebral malaria and treated at the Kenya Medical Research Institute, Clinical Research Center, Kilifi, Kenya.